The Effect of Human Platelets on Lipolytic Activity in Plasma - Vik-Mo, Harald (Thrombosis and Haemostasis, 1975)
A method for assay of lipolytic activity in platelet-poor plasma (PPP), platelet-rich plasma (PRP) and washed human platelets is presented. The lipolytic activity in PRP was about twice the activity in PPP. A significant correlation between lipolysis in platelets and platelet number was established. Molar sodium chloride strongly inhibited lipolytic activity in platelets and a washing procedure did not significantly change the lipolysis. The results indicate that a lipoprotein lipase is bound to human platelets and may play a role in metabolism of triglyceride in platelets.